The Pragmatic Suitability of the Algerian ELT Secondary School Textbooks: A Focus on Speech Acts - DENDENNE, Boudjemaa (Journal of Human Sciences, 2014)
This study investigates to what extent the Algerian ELT secondary school textbooks are pragmatically-suitable with regard to speech acts, with a focus on two of the most frequent ones:request and apology. The study aims at exploring the appropriacy and adequacy of the input at the pragmalinguistic level and the sociopragmaticone,the explicitness of that input and the metapragmatic information associated with it. All the requests and apologies that appear in the materialare identified, then coded and analysed. Findings show that although the textbooks provide a minimum of the linguistic forms used for the realisation of these two speech acts, they are rather limitedwhen it comes to associating them with the relevant contextual and cultural factors. The input is, on the whole, implicitly presented while there is paucity in the metapragmatic information that is necessary to guidethe learners to the best production of these two acts. In this respect, the material used is highly unlikely to provoke the acquisition of these two speech acts. It is, therefore, recommended that the syllabus designers should address these shortcomings